Outcomes of people with psychotic disorders in a community-based rehabilitation programme in rural India - Chatterjee, Sudipto (Royal College Of Psychiatrists, 2009)
Background There is little evidence of the feasibility, acceptability and impact of services for the care of people with psychotic disorders in low- and middle-income countries. Aims To describe the scaling up and impact of a community-based rehabilitation programme for people with psychotic disorders in a very-low-resource setting. Methods Longitudinal study of people with psychotic disorders who had been ill for an average of 8 years in a rural Indian community. All individuals received a community-based intervention package comprising psychotropic medications, psychoeducation, adherence management, psychosocial rehabilitation and support for livelihoods. The primary outcome was change in disability scores. Results The cohort consisted of 256 people with psychotic disorders (schizophrenia, bipolar affective disorder and other psychosis) of whom 236 people completed the end-point assessments (92%), with a median follow-up of 46 months. There were significant reductions (P<0.05) in the levels of disability for the cohort, the vast majority (83.5%) of whom engaged with the programme. On multivariate analyses, lower baseline disability scores, family engagement with the programme, medication adherence and being a member of a self-help group were independent determinants of good outcomes. Lack of formal education, a diagnosis of schizophrenia and dropping out of the programme were independent determinants of poor outcomes. Conclusions Community-based rehabilitation is a feasible and acceptable intervention with a beneficial impact on disability for the majority of people with psychotic disorders in low-resource settings. The impact on disability is influenced by a combination of clinical, programme and social determinants.